2018
DOI: 10.1016/j.neuroscience.2018.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Type 1a Receptors in the Subfornical Organ Modulate Neuroinflammation in the Hypothalamic Paraventricular Nucleus in Heart Failure Rats

Abstract: Inflammation in the hypothalamic paraventricular nucleus (PVN) contributes to neurohumoral excitation and its adverse consequences in systolic heart failure (HF). The stimuli that trigger inflammation in the PVN in HF are not well understood. Angiotensin II (AngII) has pro-inflammatory effects, and circulating levels of AngII increase in HF. The subfornical organ (SFO), a circumventricular structure that lacks an effective blood-brain barrier and senses circulating AngII, contains PVN-projecting neurons. We hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 62 publications
1
37
1
1
Order By: Relevance
“…These changes were accompanied by a reduction in the total number of activated (pro-in ammatory) microglia as well as reduced mRNA levels for IL-1β, IL-6 and TNF-α (61). Taken together, these previous studies pinpoint neuroin ammation, particularly microglial cell activation within the PVN, as a key underlying pathophysiological mechanism contributing to the sympathohumoral and cardiovascular complications associated with HF (23)(24)(25)(26). Given that the PVN is a key regulatory structure involved in the integration of behavioral, cardiovascular and neuroendocrine homeostatic responses (64)(65)(66), and is richly interconnected with a plethora of brain regions (32,(67)(68)(69), including the amygdala, it is reasonable to speculate that neuroin ammation could also contribute to mood and anxiety disorders associated to HF.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…These changes were accompanied by a reduction in the total number of activated (pro-in ammatory) microglia as well as reduced mRNA levels for IL-1β, IL-6 and TNF-α (61). Taken together, these previous studies pinpoint neuroin ammation, particularly microglial cell activation within the PVN, as a key underlying pathophysiological mechanism contributing to the sympathohumoral and cardiovascular complications associated with HF (23)(24)(25)(26). Given that the PVN is a key regulatory structure involved in the integration of behavioral, cardiovascular and neuroendocrine homeostatic responses (64)(65)(66), and is richly interconnected with a plethora of brain regions (32,(67)(68)(69), including the amygdala, it is reasonable to speculate that neuroin ammation could also contribute to mood and anxiety disorders associated to HF.…”
Section: Discussionmentioning
confidence: 73%
“…Lastly, it is important to note that while we report here signi cant changes in glial morphology and cytokine levels, it remains unclear whether these changes translate into altered glial function and how they might ultimately affect the pro-in ammatory state within the respective brain regions. Finally, most published studies in the eld using the congestive HF rodent model, including the present one, were performed in young adult rats (6-10 weeks), (23,26,(100)(101)(102). This is a caveat that needs to be taken into consideration, given that the incidence of HF in humans is higher in the elderly population.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In fact, SFO is a major source for de novo synthesis of Ang‐II within the brain (Sinnayah et al . ) and it has been shown that AT1 knockdown in this nucleus in HFrEF rats reduces the expression of TNF‐α, IL‐1β, CD68 (a marker of microglial activation) and c‐Fos (a marker of neuronal activation) in the PVN, diminishes plasma NA, and slightly restored cardiac function, without affecting plasma cytokines or Ang‐II (Yu, ). However, the contribution of SFO in HFpEF pathophysiology is completely unknown (Table ), despite evidence strongly suggesting that it could play a major role in HFpEF pathophysiology.…”
Section: Introductionmentioning
confidence: 99%